Karakter Han Dengan Radikal 示 Dalam Shuowenjiezi: Klasifikasi, Aktivitas Penyembahan, Perbandingan Dengan Kamus Xiandai Hanyu - Sahertian, Diana C. (Bina Nusantara University, 2011)
The writing system used in the Chinese language is different from the Latin characters used in the Indonesian language. While the Latin characters represent sounds, the Han characters of the Chinese language represent meanings. Some Han characters have a component called a ‘radical’. This paper discusses Han characters with the 示 radical in Shuowen jiezi. The first part consists of the classification of such characters based on their structure and meaning. The second part discusses the worship practices on which the characters are based. The last part of this paper compares these Han characters to those with the same 示 radical in the Xiandai Hanyu Dictionary.